Walk on the wild side [modular robot motion]. - Yim, M. (IEEE Robotics and automation magazine)
Designers of the PolyBot robot system solve the challenges of locomotion by mimicking locomotion in the animal world. PolyBot is a robot system made of many repeated simple modules. These modules can be connected together to form a variety of shapes to form a new system enabling a variety of functionalities.